Implementation of the Effect of Price and Service Quality on Honda Car Purchasing Decisions in Tegal (Case Study of PT. Dova Putra Manunggal Sejati) - Sri Undartik; Arie Nastio Reza; Khalid Iskandar; Fitriana Kartika Sari (CV. Rayyan Dwi Bharata, 2023)
To maintain a good name in the eyes of its customers, a company competes in terms of service or price. A good and reliable payment system will increase the number of buyers, making it easier for business actors to achieve their goals to get maximum profit. Not only that, the price also carries a markup that is specifically related to customer complaints. The term